Rheological Properties of Polyurethane-Based Magnetorheological Gels - Zhang, Guang; Li, Yancheng; Wang, Huixing; Wang, Jiong (Frontiers in Materials, 2019)
This paper investigates the impact of mass fractions of carbonyl iron particles (CIPs) on the rheological properties of magnetorheological (MR) gels. Polyurethane-based MR gels with different weight fraction of CIPs, i.e. 40%, 60% and 80%, were firstly prepared by mechanical mixing, respectively. The shear stress and viscosity as a function of shear rate under different magnetic field intensities are measured and discussed. It is found that the shear stress increases with mass fraction under applied magnetic field. The dynamic properties of MRGs are obtained under oscillatory shear test. The influences of strain amplitude and frequency on the dynamic properties of samples at different magnetic field conditions are discussed. The results demonstrate that the increase of CIPs mass fraction leads to the increase of storage modulus and the reduction of the loss factor.